2020
DOI: 10.1093/jac/dkaa049
|View full text |Cite
|
Sign up to set email alerts
|

Lung penetration, bronchopulmonary pharmacokinetic/pharmacodynamic profile and safety of 3 g of ceftolozane/tazobactam administered to ventilated, critically ill patients with pneumonia

Abstract: Objectives Ceftolozane/tazobactam is approved for hospital-acquired/ventilator-associated bacterial pneumonia at double the dose (i.e. 2 g/1 g) recommended for other indications. We evaluated the bronchopulmonary pharmacokinetic/pharmacodynamic profile of this 3 g ceftolozane/tazobactam regimen in ventilated pneumonia patients. Methods This was an open-label, multicentre, Phase 1 trial (clinicaltrials.gov: NCT02387372). Mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 45 publications
0
49
1
Order By: Relevance
“…However, despite the first limitation, the estimation of omadacycline ELF exposure using a population PK model, which was developed by comodeling plasma and ELF concentration data, represented a robust approach. With regard to the second limitation, while data evaluating ELF exposures for antimicrobial agents in infected patients are limited (24)(25)(26)(27)(28) and more challenging to obtain, future studies in omadacycline-treated patients would be useful to determine if ELF exposure in patients is different from that in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the first limitation, the estimation of omadacycline ELF exposure using a population PK model, which was developed by comodeling plasma and ELF concentration data, represented a robust approach. With regard to the second limitation, while data evaluating ELF exposures for antimicrobial agents in infected patients are limited (24)(25)(26)(27)(28) and more challenging to obtain, future studies in omadacycline-treated patients would be useful to determine if ELF exposure in patients is different from that in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Interim safety results from a Phase 1 PK study reported that twice the standard dosing of ceftolozane/tazobactam, or 3 g every 8 h, was safe and generated sufficient exposure in twelve critically ill pneumonia patients with a mean creatinine clearance of 134.6 mL/min [ 70 ]. The exposures from this increased regimen were confirmed to be adequate upon completion of this study [ 71 ]. A population pharmacokinetic analysis that took ARC into consideration was performed for imipenem/relebactam [ 72 ].…”
Section: Effects On Antibiotic Therapymentioning
confidence: 78%
“…Of these, 1481 and 1455 ceftolozane and tazobactam plasma observations, respectively, were obtained from 305 adult patients participating in the ASPECT‐NP study (MK7625A‐008, Supplemental Table S1). ELF data were obtained from 2 phase 1 studies: 1 study was conducted in healthy volunteers (CXA‐ELF‐10‐03) 22 and the other in critically ill patients with confirmed or suspected pneumonia (CXA‐ICU‐14‐01) 24 . In addition to plasma samples, these 2 studies collected bronchoalveolar lavage samples to measure ceftolozane and tazobactam concentrations in ELF from each patient at 1 of 5 predefined times (1, 2, 4, 6, or 8 hours after the start of infusion).…”
Section: Methodsmentioning
confidence: 99%
“…Model 2 assumed an ELF compartment with mass transfer between the plasma and ELF compartments, and model 3 was a hypothetical link model without mass transfer and assumed an influx rate constant from plasma‐to‐ELF compartments (K 1E ), an elimination rate constant from the ELF compartment (K E0 ), and that V3 was equal to V1. An exploratory data analysis suggested that plasma and ELF data were more variable in critically ill patients with confirmed or suspected pneumonia compared with healthy participants 22,24 . As a result, the base structural models for ceftolozane and tazobactam were refined further by estimating IIV with K 1E separately for healthy participants and patients with pneumonia.…”
Section: Methodsmentioning
confidence: 99%